(untitled) (Intent Research Scientific Journal, 2023)
In the ever-evolving world of software development, maintaining high standards is essential for creating robust, efficient, and scalable applications. These standards serve as guidelines and best practices that ensure your software is maintainable, reliable, and interoperable. In this article, we will explore the ways to use standards in software design to achieve these goals.